2013
DOI: 10.2174/1874941001003010092
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Cue Exposure Therapy for the Treatment of Addictive Disorders: A Review Update

Abstract: Abstract:Objectives: To evaluate the role of cue exposure therapy in addiction treatment.Methods: A Pubmed/PsycInfo literature search was performed for cue exposure treatments for addictions from 2002 to 2009. Findings:We located sixteen cue exposure therapy studies involving multiple addictions that were conducted between 2002 and 2009. Four of these studies consisted of clinical efficacy trials that assessed drug use after Cue Exposure Therapy (CET). In three of the four trials, cue exposure was no better or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Treatments that specifically focus on cues, such as cue exposure therapy have been disappointing most notably due to the context specificity of extinction (Conklin & Tiffany, 2002; Havermans & Jansen, 2003; Martin, LaRowe, & Malcolm, 2010). Mainstay smoking cessation treatments may propagate smoking cue-induced craving by counseling smokers to avoid smoking cues or to suppress the craving through alternative behaviors (Fiore & Jaen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments that specifically focus on cues, such as cue exposure therapy have been disappointing most notably due to the context specificity of extinction (Conklin & Tiffany, 2002; Havermans & Jansen, 2003; Martin, LaRowe, & Malcolm, 2010). Mainstay smoking cessation treatments may propagate smoking cue-induced craving by counseling smokers to avoid smoking cues or to suppress the craving through alternative behaviors (Fiore & Jaen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests potential for exercise to aid smokers in coping with cue-induced craving where other methods have failed, an important possibility given that cue-induced craving is not alleviated by nicotine replacement (Tiffany, Cox, & Elash, 2000) and can continue much longer than abstinence-induced withdrawal. Moreover, although two studies have demonstrated reduction in cue-induced craving during treatment with varenicline (Brandon et al, 2011; Franklin et al, 2011) other studies have not found this effect (e.g., Hitsman et al, 2013); and, behavioral techniques aimed at reducing cue-induced craving have also consistently failed (Conklin & Tiffany, 2002a, 2002b; Martin et al, 2010). The current finding is in line with other studies examining the impact of physical activity during very brief abstinence (several hours) on cue-induced craving.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbating the difficulty of quitting, smokers readily report that confrontation with cues associated with smoking is another vital aspect of their inability to stay quit (Shiffman et al, 2007). Unfortunately, past attempts to attenuate such cue-reactivity through nicotine replacement and/or behavioral exposure treatment have consistently failed (Conklin & Tiffany, 2002a; Ferguson & Shiffman, 2009; Martin, LaRowe, & Malcolm, 2010). Therefore, treatment adjuncts capable of reducing not only abstinence-induced craving and negative mood, but cue-induced craving as well, may significantly enhance current smoking cessation treatments.…”
mentioning
confidence: 99%
“…CET, however, has limits on the nature of environmental cues that can be simulated, the degree of sense of "immersion" and reality, and has also shown decreased efficacy over time. Thus a virtual reality variation of cue exposure treatment, the Virtual Environment-CET (VR-CET), has been developed as an alternative to CET [80,81]. To explore VR-CET treatment effects fMRI was conducted on eight adolescents who were cigarette smokers before and after they received VR-CET [81].…”
Section: Addictionmentioning
confidence: 99%
“…Thus a virtual reality variation of cue exposure treatment, the Virtual Environment-CET (VR-CET), has been developed as an alternative to CET [80,81]. To explore VR-CET treatment effects fMRI was conducted on eight adolescents who were cigarette smokers before and after they received VR-CET [81]. (No comparison treatment was assessed.)…”
Section: Addictionmentioning
confidence: 99%